Seasonal effect on semen quality of Limousine and Simmental bulls - F. R. Hapsari; D. Samsudewa; E. T. Setiatin; Y. S. Ondho; A. Setiaji; T. Harsi; I. Z. Irfan; O. Syamsono; E. Sukmawati (Diponegoro University, 2022)
This study aimed to determine the effect of breed and season on the semen quality of AI bulls. The material used was n= 78,648 records of ejaculated semen from 85 Limousine and 88 Simmental bulls collected between period 2010 and 2020. Semen qualities evaluated in the study were: ejaculate vol-ume (Vol), pH, individual sperm motility (ISM), sperm concentration (SC), and post-thawing motility (PTM). The data was analyzed by using a MIXED model with breeds and seasons as fixed effects and animals as random effects. The seasons were significant (p<0,05) on Vol, ISM, SC, and PTM, then the interaction between season and breed was affected on Vol, SC, and PTM. Simmental bulls generally showed better semen qualities than Limousine bulls. Further, the same result showed significant differ-ences in each season. The Vol, ISM, SC, and PTM of Simmental were 6.48 ± 1.26, 64.22 ± 1.16, 1,108 ± 0.46, and 42.19 ± 0.38, respectively. The increase of Vol and SC in the humid season has not propor-tionally affected ISM.